Synthetic Calcium Phosphate Ceramics as a Potential Treatment for Bisphosphonate-Related Osteonecrosis of the Jaw - Paulo, Siri (2019)
(1) Background: Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is one of the most often seen side effects in patients treated with nitrogen-containing bisphosphonates (BPs), a post-surgical non-healing wound condition. Since calcium phosphate (CP) compounds are able to adsorb zoledronate (ZOL) when used as a drug delivery vehicle, we aimed to verify if these ceramics might have a potential protective effect for soft tissues surrounding surgical osseous wounds. (2) Methods: The chemical reaction between ZOL and CP compounds was evaluated through ultraviolet-visible spectroscopy and elemental analysis. A primary culture of human gingival fibroblasts (HGF) was established as a model to evaluate the cytotoxicity of the association of ZOL (5-500 μM) and of ZOL/biphasic calcium phosphates (BCP). Metabolic activity, cell viability, types of cell death, the cell cycle through, and the migration ability of human gingival fibroblasts were evaluated. (3) Results: ZOL was adsorbed by biphasic calcium phosphate compounds in an aqueous solution. The HGF were sensitive to ZOL toxicity; nevertheless, ZOL/BCP showed a significant protective effect regarding metabolic activity, cell viability, and cell migration. (4) Conclusions: BCP interaction with ZOL reduces or abolishes its toxicity in HGF. This finding represents a potential solution for BRONJ in the case of patients undergoing therapy with ZOL.